Teaching Cognitive Biases in Clinical Decision Making: A Case-Based Discussion - Keng Sheng Chew; Jeroen van Merrienboer; Steven Durning (Association of American Medical Colleges, 2015)
Abstract Introduction This resource consists of five cases set in the emergency department and intended to instruct participants in identifying inherent cognitive biases as well as considering alternative diagnoses (thinking outside the box). The cases are embedded with cognitive biases commonly encountered in the clinical setting. Each case is framed in such a way as to lead participants into an obvious diagnosis. However, besides the obvious diagnosis, there are subtle clinical cues that point to the likelihood of another, more urgent or life-threatening diagnosis that must be considered. Undergirding the construct of these cases is the idea that if participants slow down and reflect on questions like "Is there any life-or-limb threat that I need to rule out in this patient?", "If I am wrong, what else could it be?", or "Do I have sufficient evidences to support or exclude this diagnosis?", they are more likely to avoid these cognitive biases and be able to pick up the second diagnosis. Methods These cases were implemented with final-year medical students to evaluate the effectiveness of a small-group tutorial on the influence of cognitive biases in clinical decision-making as well as a discussion on cognitive debiasing strategy. During the first week of their emergency medicine rotation, 21 medical students were given the small-group tutorial. Then, towards the end of their 2-week emergency medicine rotation, they were given the five cases. In each case, a question on generating differential diagnoses and another question on one or two aspects of patient care were asked. Results Two similarly sized groups of final-year medical students participated in our quasi-experimental study. The intervention group was assigned to receive the educational intervention, while the control group received a tutorial on basic electrocardiography. Postintervention, both groups received an assessment on clinical decision-making based on the five case scenarios. Students in the intervention group scored significantly better than students in the control group. Discussion These clinical cases can serve as an introductory tool to teach cognitive biases and cognitive debiasing strategies. Students can then learn more about how these cognitive biases affect actual clinical decisions in the wards, during morbidity and mortality meetings, as well as the steps they should take or could have taken or may have observed being taken by the doctors around them as cognitive debiasing strategies.